Features Inheritance with Reference to Standard Arabic: A Minimalist Analysis - Alrashdan, Imran (DIRASAT: EDUCATIONAL SCIENCES, 2017)
This paper attempted to show that Chomsky’s Features Inheritance (2005, 2008) is a systematic operation in- and applicable to Standard Arabic. Syntactic features including phi-features and Tense are encoded in phasal heads such as C and v. These features according to Chomsky percolate to a substantive lower non-phasal head which acts as a probe looking for a goal with matching interpretable features. Hence, all uninterpretable features on both heads, i.e. the probe and the goal, get checked and are assigned interpretable values via the probe-goal analysis. In other words, the phasal heads C and v (rather than T and V) can probe and locate a close goal so the uninterpretable features will be assigned values before spell-out. Failure to assign interpretable values to these features will lead the derivation to crash. Finally, the study proposed that valued features are sent to their criterial position in the PF rather than prior to spell-out. In this article, Standard Arabic is taken as a case study to demonstrate that features inheritance is a systemized operation like any other syntactic operation and to show that Chomsky’s proposal of features inheritance is valid and applicable to Standard Arabic.